The Students Mastery of Indonesian Affixes in Telling Story based on Age - Muazizah, Risalatul; Yulianto, Bambang; Sodiq, Syamsul (International Journal for Educational and Vocational Studies, 2020)
Affix mastery is the ability of individuals to master prefixes, infixes, suffixes, confixes, and combinations of affixes. Child language mastery is related to the age aspect. This study aims to describe the mastery of Indonesian affixes based on age. This type of research is descriptive cross sectional with 30 junior high school / MTs students aged 12, 13, and 14 years as research subjects. Data collection techniques used were listening, field note, recording, and testing. The results of this study indicate there is an increase in mastery of Indonesian affixes by students aged 12, 13, and 14 years both in terms of type of affix, frequency, and value of affixes. Increased stable affix mastery based on age is found in prefixes and affix combinations. Based on this, it can be concluded that each age of the child increases, so does the level of mastery of the child's affixes.